On Shareholder Unanimity in Large Stock Market Economies - Hart, Oliver D. (Econometrica, 1979)
In an economy with complete markets, the owners of a firm will unanimously desire the firm to maximize profits if it is a perfect competitor. We generalize this result to an economy with incomplete markets. We show that if competitive conditions prevail-that is, if each firm is negligible relative to the aggregate economy-a firm's shareholders will want the firm to maximize the (net) market value of its shares. This result holds whether or not the so-called spanning condition is satisfied. However, while there may be agreement about what goal the firm should pursue, there may be disagreement among shareholders about how best to pursue this goal.